2010
DOI: 10.1007/s11205-010-9632-5
|View full text |Cite
|
Sign up to set email alerts
|

The Eudaimonic and Hedonic Components of Happiness: Qualitative and Quantitative Findings

Abstract: Happiness, Meaning, Satisfaction with life, Life domains, Mixed-method approach,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
298
3
56

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(406 citation statements)
references
References 55 publications
28
298
3
56
Order By: Relevance
“…The subjects were Caucasian adults of Polish nationality living in large and medium-sized cities. Hedonic and eudemonic well-being are quite strongly positively correlated (Delle Fave et al 2011;Fowers et al 2010;Schueller and Seligman 2010). Although this study focuses on the eudemonic well-being, the hedonic perspective should also be included as there is a dearth of research linking the two well-being aspects in the context of work.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects were Caucasian adults of Polish nationality living in large and medium-sized cities. Hedonic and eudemonic well-being are quite strongly positively correlated (Delle Fave et al 2011;Fowers et al 2010;Schueller and Seligman 2010). Although this study focuses on the eudemonic well-being, the hedonic perspective should also be included as there is a dearth of research linking the two well-being aspects in the context of work.…”
Section: Methodsmentioning
confidence: 99%
“…We hoped to determine those dimensions that participants considered important to their understanding of happiness to determine what, in their opinions, constitutes happiness and to measure their individual experience of well-being. We aimed to close the gap in well-being research noted by Delle Fave et al (2011), who identified a dearth of qualitative and exploratory research on lay conceptions of happiness, especially with bigger samples. We use Diener's (2000) conception of subjective well-being.…”
Section: Subjective Well-beingmentioning
confidence: 99%
“…Most studies have used scales based on Western philosophical and psychological perspectives (Delle Fave et al 2011). This is a serious limitation and more exploratory studies are needed to create a more culture-fair methodology.…”
Section: Lay Conceptions Of Happinessmentioning
confidence: 99%
See 2 more Smart Citations